ARDL bound test approach for co-integration between FDI, human capital and innovation activities - Ricky Jores; Law, Siong Hook (Penerbit Akademia Baru, 2016)
FDI can be beneficial in term of creating spillover in the hosts’ country, but there is no direct evidence to confirm that FDI affects innovation activities in Malaysia. Innovation means fresh thinking and approaches that add value to consistently create wealth and social welfare. This study examines the effect of inward FDI and human capital on innovative activities thus to provide an evidence on the interaction term between inward FDI and human capital using the ARDL bound test approach. The results show that inward FDI is negatively related with the innovation activities in the short run but is positively related in the long run. The presence of the human capital as an absorptive tool helps in mediating the effects of inward FDI on innovative activities in Malaysia. Meanwhile, it suggests that the injection of inward FDI require human capital to facilitate the innovation process in order to enhance the innovation capacity. To raise the contribution of inward FDI and human capital on innovative activities, there is a need to shift from the old trend assembly of goods and products into the knowledge-based economy that concentrates on research, knowledge and skills.